The Ethics Of Recruitment And Selection Practices (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Recruitment and selection is a backbone of human  resource management (HRM) practices and its incorporation to business is vital to organizational success.  When people sense the difficulty in cracking the interview it  is related to unfairness and unethical hiring during the  selection process. This paper examines the difference  between ethics, Morals and values which people boast  about while making important business decisions like  hiring. A decision of recruitment that is becoming the  burden is exercising unethical hiring practices. Most  unethical hiring practices occur when a company decides  to hire an employee based on his or her race, color, religion, appearance sex or national origin. This paper  examines the patterns which people adapt for hiring to face  the challenge and beat the competition in the industry. A secondary research has been conducted with an objective  to analyze why people engage in discriminatory acts while  hiring. It has been found that employees sometimes feel  pressure to sacrifice ethics in today's competitive market place due to increased expectations and cutbacks. unethical hiring during the selection process. It has been Understanding the major causes of unethical practices in  the workplace will help us become sensitive to signals of  escalating pressure to compromise our values. These  values change occasionally and are not lived by, for which  the excuse is always financial but that is not the cause of  adapting unethical behavior.
Keywords: HRM Practices; Organization; unethical hiring practices; hiring discrimination; behavior